STRUKTUR KOMUNITAS PLANKTON DI KAWASAN WANA WISATA CURUG SEMIRANG KECAMATAN UNGARAN BARAT, SEMARANG - Delliana Ratna Sari; Jafron Wasiq Hidayat; Riche Hariyati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Objective of the study was to know the structure of plankton community and to know the influential physical and chemical factors in the structure of plankton community in Semirang. This research was conducted on 6 stations with different water body condition. Results showed that the number of plankton species obtained were 12 species in the Bacillariophyta Division. Plankton species that widely found were Achnanthes sp, Cymbella tropica and Cocconeis pediculus. The relative abundance index categorized into the dominant species category. The plankton diversity index were mostly included in the moderate category. Similarity index belongs to the category of even distribution, none dominance of a kind. The similarity index is mostly included in the high category. Physical and chemical factors in these waters have good water quality for plankton life. Keywords: plankton community structure, freshwater, ecotourism waterfall Semirang